Dynamic Evolution Law of Overburden Rock in Shallow-Buried Super-High Fully Mechanized Working Face and Determination of Support Strength - Yingjie Liu; Haijun Wang; Qingjie Qi; Anhu Wang; Youxin Zhao (Shock and Vibration)
The objective of this study was to reveal the law of overburden movement and stress evolution during the mining of super-high fully mechanized mining faces. Based on the 12401 fully mechanized mining face of Shangwan Coal Mine in Shendong, this study conducted research and analysis using the methods of similarity simulation experiment, numerical simulation, and field measurement. The results showed that the maximum and minimum principal stresses in the coal seam in front of the working face are concentrated with the advance of the working face. The degree of stress concentration increases with the increase in the advancing range, and the concentration degree of the maximum principal stress and the change gradient is greater than that of the minimum principal stress. But the range of the peak lead coal wall is lower than that of the minimum principal stress of the peak lead coal wall. The phenomenon of stress recovery exists in the goaf. With the increase in the advancing range of the working face, the degree of stress recovery gradually increases, and the degree of maximum principal stress recovery is higher than that of the minimum principal stress recovery. The large fractures observed near the working face are closely related to the underground pressure, relatively large fractures appear on the surface, and the fractures become narrower near the two pathways. Only caving and fissure zones exist in the thin bedrock overburden, and the bending subsidence zone changes with the bedrock thickness. The support strength of the hydraulic support should not be less than 1.47 MPa. This research on the overburden movement and stress evolution law of a super-high fully mechanized mining face can provide theoretical guidance for the exploitation and utilization of extrathick coal seam resources. It has broad engineering prospects.